Enhanced coordination of care to reduce medication risks in older home care clients in primary care: A randomized controlled trial - Terhi Toivo; Marja Airaksinen; Maarit Dimitrow; Eeva Savela; Katariina Pelkonen; Valtteri Kiuru; Tuula Suominen; Mira Uunimäki; Sirkka-Liisa Kivelä; Saija Leikola; Juha Puustinen (BioMed Central Ltd., 2025)
Background: As populations are aging, a growing number of home care clients are frail and use multiple, complex medications. Combined with the lack of coordination of care this may pose uncontrolled polypharmacy and potential patient safety risks. The aim of this study was to assess the impact of a care coordination intervention on medication risks identified in drug regimens of older home care clients over a one-year period.
Methods: Two-arm, parallel, cluster randomized controlled trial with baseline and follow-up assessment at 12 months. The study was conducted in Primary Care in Lohja, Finland: all 5 home care units, the public healthcare center, and a private community pharmacy. Participants: All consented home care clients aged > 65 years, using at least one prescription medicine who were assessed at baseline and at 12 months. Intervention: Practical nurses were trained to make the preliminary medication risk assessment during home visits and report findings to the coordinating pharmacist. The coordinating pharmacist prepared the cases for the triage meeting with the physician and home care nurse to decide on further actions. Each patient’s physician made the final decisions on medication changes needed.
Outcomes were measured as changes in medication risks: use of potentially inappropriate medications and psychotropics; anticholinergic and serotonergic load; drug-drug interactions.
Results: Participants (n = 129) characteristics: mean age 82.8 years, female 69.8%, mean number of prescription medicines in use 13.1. The intervention did not show an impact on the medication risks between the original intervention group and the control group in the intention to treat analysis, but the per protocol analysis indicated tendency for effectiveness, particularly in optimizing central nervous system medication use. Half (50.0%) of the participants with a potential need for medication changes, agreed on in the triage meeting, had none of the medication changes actually implemented.
Conclusion: The care coordination intervention used in this study indicated tendency for effectiveness when implemented as planned. Even though the outcome of the intervention was not optimal, the value of this paper is in discussing the real world experiences and challenges of implementing new practices in home care.